Pelaksanaan Metode Muraja’ah Pada Program Tahfiz Al-Qur’an di MAN 2 Bukittinggi - Selvina Selvina; Charles Charles; Wedra Aprison; Deswalantri Deswalantri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this research is 1) to find out the implementation of the muraja’ah method inthe program at MAN 2 Bukittinggi. 2) to determie the supporting factors and inhbiting factors in the implementation of the muraja’ah method in the Al-Qur’an tahfiz program. The type of research used in this research is qualitative research with data collection techniques using observation, interviews, and documentation with data analysis tecniques using data reduction, data display and conclutions. Based on the results of research on the implementation of muraja’ah in the tahfiz program at MAN 2 Bukittinggi. Based on resarch of the implementation of Tahfiz at MAN 2 Bukittinggi using the muraja’ah method, there are three steps of the muraja’ah, namely: 1)preparation, 2) Implementation of the muraja’ah method, and 3) Evaluation. The supporting factors for the implementation of in the muraja’ah tahfiz method at MAN 2 Bukittinggi are school resposes the quiqly respin to the potential the exist in students. Obstacle factors implementation muraja’ah tahfiz method are time, teaching staff, and motivation from students.